IMPLEMENTATION OF BASEL III IN THE EUROPEAN BANKING SECTOR - Ioana Sbarcea (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In this work, which is part of a larger research project aimed at the expected impact of Basel III on commercial banks in Romania, I decided to analyse the implementation and transposition of the new international prudential requirements into European regulations, which are of particular interest for the Romanian banking sector. I started this analysis by highlighting the peculiarities of the European banking sector at aggregate level, but also as a cross-country survey, to later highlight the views of European regulations on prudential supervision and differences to international regulations.